The impact of COVID-19 on Australian plastic and reconstructive surgery trainees: a survey study - James Cockburn; Noah Betar; Bavahuna Manoharan (Australasian Journal of Plastic Surgery)
**Introduction**: The COVID-19 pandemic had a significant impact on the training of plastic and reconstructive surgeons and the wellbeing of surgical trainees internationally. The aim of this study was to evaluate the impact of the COVID-19 pandemic on Australian plastic and reconstructive surgery trainees.